APPLICATION OF BIM TECHNOLOGIES IN CONSTRUCTION PROJECT MANAGEMENT - Georgy Kara (Modern American Journals, 2025)
The article discusses the prospects for using building information modeling (BIM) technologies in the context of construction project management. An analysis of the benefits provided by BIM at various stages of the life cycle of a construction project is conducted, and potential barriers and risks associated with the implementation of this technology are identified. Examples of successful integration of BIM into project management practice are presented. The role of BIM in ensuring increased transparency, efficiency and sustainability of the construction industry is emphasized.
Keywords: BIM, construction project management, digitalization, information modeling, building life cycle.